THE EFFECT OF POLITICAL CONNECTIONS, MULTIPLE DIRECTORSHIPS, COMPANY PERFORMANCE, AND TAX PLANNING ON EARNING MANAGEMENT IN REGISTERED STATE-OWNED COMPANIES AT BEI 2019-2022 - Fizal Alharis; Razif; Mursidah; Muhammad Yusra (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze the effect of political connections, multiple directorships, company performance, and tax planning on earnings management. This study used a sample of BUMN companies listed on the IDX in 2019-2022 as many as 44 samples using purposive sampling techniques totaling 11 companies with observations for 4 years. The analysis technique used here is to use multiple linear regression analysis which is processed using the IBM SPSS 26 program. The results of the study using the t test (partial) show that the variables of political connections, multiple directorships, solvency, profitability, and tax planning have no significant effect on the earnings management variable. While the liquidity variable has a significant positive effect on earnings management.